1999
DOI: 10.1080/00071669987403
|View full text |Cite
|
Sign up to set email alerts
|

Influence of stocking density on behavioural, health and productivity traits of turkeys in large flocks

Abstract: 1. The effect of stocking density on welfare traits of turkeys was studied in 2 experiments. In each experiment 2,633 sexed BUT turkey poults were assigned to 3 rooms, 135 m2 with 1 treatment per room. Because of the large flock size (675,878 and 1080 birds in T1, T2 and T3 respectively) treatments were not replicated 2. Floor space allowances varied according to treatment; for the males: 24 dm2, 18.5 dm2 and 15 dm2 until week 12 and 40 dm2, 31 dm2 and 25 dm2 from week 12; for the females: 16 dm2, 12.3 dm2 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
66
0
6

Year Published

2004
2004
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(87 citation statements)
references
References 19 publications
15
66
0
6
Order By: Relevance
“…Wechsler & Schmid (1998) found that aggressive interactions were significantly increased in multiple-male groups of Japanese quail (Coturnix japonica). The abnormal behaviour patterns observed at the higher stocking rates agree with findings in poultry where high stocking rates had a negative influence on the reproduction performance and well-being of laying hens (Hughes & Wood-Gush, 1977;Blokhuis & Wiepkema, 1998;Sherwin & Kelland, 1998;Martrenchar et al, 1999;Savory et al, 1999;Bilcik & Keeling, 2000;Klein et al, 2000). The high stocking rates of 150 birds, 141 birds and 210 birds/ha also contributed to an increased incidence of homosexual behaviour and feather pecking, both during the breeding and the non-breeding periods.…”
Section: Discussionsupporting
confidence: 78%
“…Wechsler & Schmid (1998) found that aggressive interactions were significantly increased in multiple-male groups of Japanese quail (Coturnix japonica). The abnormal behaviour patterns observed at the higher stocking rates agree with findings in poultry where high stocking rates had a negative influence on the reproduction performance and well-being of laying hens (Hughes & Wood-Gush, 1977;Blokhuis & Wiepkema, 1998;Sherwin & Kelland, 1998;Martrenchar et al, 1999;Savory et al, 1999;Bilcik & Keeling, 2000;Klein et al, 2000). The high stocking rates of 150 birds, 141 birds and 210 birds/ha also contributed to an increased incidence of homosexual behaviour and feather pecking, both during the breeding and the non-breeding periods.…”
Section: Discussionsupporting
confidence: 78%
“…It is known that increasing the stocking density leads to changes in behaviour in both commercial (Hall, 2001) and experimental conditions (Blokhuis and van der Haar, 1990;Lewis and Hurnik, 1990;Marttenchar et al, 1997). In general, increasing the number of birds per unit area was found to increase the incidence of agonistic behaviour and reduce the amount of time spent lying or resting.…”
Section: Introductionmentioning
confidence: 89%
“…Opposed to Jong et al (2003), no significant differences in the laying down behavior due to feeding restriction were observed in the present experiment. However, this disparity may be partially explained by the results of Martrenchar et al (1997), who concluded that the increase in bird density may negatively affect welfare, as determined by physiological and productive parameters.…”
Section: Effect Of Feeding Strategy On Behavioral Responsesmentioning
confidence: 80%
“…Results showed that qualitative feed restriction resulted in higher welfare standards, and this research work has been used to subsidize welfare regulations. Martrenchar et al (1997), studied stocking densities and behavioral responses of broilers, and concluded that 43 kg/m 2 negatively affected welfare, as measured by behavioral, physiological, and productive parameters in comparison to a stocking density of 27 kg/m 2 . The objective of the present research work was to study the influence of environmental temperature on the behavioral responses of female broiler breeders.…”
Section: Introductionmentioning
confidence: 99%